Nutritional Status and Severity of Pneumonia among Inpatient of Children Under Five Years - Kharisma, Dayu Swasti; Zahra, Balqis Al Sakina (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2022)
Background: The prevalence of pneumonia in developing countries continues to increase, especially in Indonesia. One of the factors that influence the severity of pneumonia is nutritional status. Malnutrition increases susceptibility to infection. Purposes: This study aimed to determine the relationship between nutritional status and pneumonia severity in children under five. Methods: This research was an analytic study with a cross-sectional design. The data were taken from the medical records of pneumonia patients under five years of age who were hospitalized at the Infectious Disease Hospital Prof. Dr. Sulianti Saroso for January 2018 to October 2019. Bivariate analysis was performed using the chi-square test. Results: Out of 68 patients who met the inclusion criteria, the highest age range was 0-11 months (50%), the most gender was female (55.9%), the group with the highest cases was the severe pneumonia group (73.5%), the most nutritional status was abnormal nutrition (55.9%). There are 86.8% of patients with abnormal nutritional status suffer from severe pneumonia. Conclusion: There is a relationship between nutritional status and pneumonia severity.